Dance education in Ireland : an examination of Smith-Autard's art of dance model in teacher education and the Irish primary school curriculum - Tanham, Gabrielle (Trinity College (Dublin, Ireland). School of Education, 2015)
A revised primary school curriculum was introduced to Irish schools in 1999. In that curriculum, dance is acknowledged as an area of arts education but delivered in physical education (Department of Education and Science, 1999a). Content and methodologies for the creative dance strand typify Laban’s (1948) educational model (Fitzpatrick, 2000). Successive Arts Council reports (Benson, 1979; Brinson, 1985; Leatherdale and Todd, 1998; Marzin, 2003) point to serious deficits in dance education in the Irish educational system. O’Dowd's (2006) study of the implementation process of the primary school dance strand indicates that less than one per cent of primary schools in Ireland delivered the dance syllabus in 2005.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin